Igual como marcador discursivo en el habla de Santiago de Chile: función pragmáticodiscursiva y estratificación social de su empleo - San Martín, Abelardo (Boletín de Filología, 2004)
In this article the pragmatic function and the social stratification ofusage of the particle igual as discourse marker in Santiago de Chile'scolloquial Spanish is analiyzed. On the one hand, the function ofthis particle in oral discourse beyond its grammatical value is studiedand, on the other hand, its frequency of usage in a socially stratifiedsample of speakers from this capital city is determined. In addition,the possibility of the study of discourse markers as sociolinguisticvariables is discussed. The results of the analysis of the pragmaticfunction of this discourse marker revealed that it functions asreformulador de distanciamiento, a term coined by Portolés (2001)for a kind of concessive conjunct. The comparison of igual withother functionally equivalent discourse markers attested in the corpuslike de todas maneras y en todo caso showed that out of 554ocurrences of the reformulador-de-distanciamiento function, 533 casesof igual were attested against 17 of de todas maneras and four ofen todo caso. The analysis of the relationship between social featuresand the usage of the discourse marker igual showed that its usagecorrelates very closely with the age and social class of speakers.Thus, young speakers, especially female ones, from the middle classare more inclined to use igual than the rest of the subjects of thesample. Finally, the role if igual as a discourse marker is interpretedas an instance of grammaticalization of an adverbial particle.